EFFECT OF BAND LIGATION ON PORTAL HYPERTENSIVE GASTROPATHY AND DEVELOPMENT OF FUNDAL VARICES - Sarwar, Shahid; Khan, Anwaar A; Alam, Altaf; Butt, Arshad Kamal; Shafqat, Farzana; Malik, Kashif; Ahmad, Irfan; Niazi, Aamir Khan (Journal of Ayub Medical College Abbottabad, 2006)
Background: Use of endoscopic therapies for esophageal varices has resulted in increased prevalence of fundal varices and severe portal hypertensive gastropathy. This study was meant to compare the effect of band ligation and sclerotherapy on development of fundal varices and portal hypertensive gastropathy. Methods: Patients with esophageal varices presenting in the endoscopy unit of Shiakh Zayed Hospital, with at least one previous endoscopy were included. Patient’˜s past record was reviewed for findings and type of treatment given for varices during first endoscopy, number of endoscopies till date, number of esophageal varices band ligation (EVBL) or sclerotherapy sessions. All patients underwent upper GI endoscopy and findings were recorded. Type of treatment patient rendered during first endoscopy either EVBL or sclerotherapy was correlated to the presence of fundal varices and severity of portal hypertensive gastropathy observed on present endoscopy, using Chi square test (Ï‡2). Results: Eighty one patients were included. Mean age of patients was 48.70+ 12.63. Esophageal varices band ligation was carried out during first endoscopy in 49 (60.5%) patients and sclerotherapy in 31 (38.2%) patients. On fresh endoscopy, fundal varices were seen in 25 (30.8%) patients. Severe portal hypertensive gastropathy was found in 26 (32.1%) and mild in 54 (66.7%) patients. Severity of portal hypertensive gastropathy and presence of fundal varices in recent endoscopy was significantly more in patients with EVBL in first endoscopy. Conclusion: Band ligation of esophageal varices is associated with more frequent development of fundal varices and worsening of portal hypertensive gastropathy compared to sclerotherapy. Key Words: Baveno scoring, Esophageal varices band ligation, Portal hypertensive gastropathy,